Image of Hercules by Dracontius: On political interpretation of mythological poems (Romulea 2 & 4) - I. M. Nikolsky (Шаги, 2024)
This paper deals with the problem of political interpretation of the works of Dracontius, a Roman poet of the late 5th century from Carthage. The thesis about the socio-political background of his poems has become increasingly widespread in recent years. The grounds for this are provided by numerous references in his works to contemporary events: the formation of the Vandal kingdom in North Africa, formerly Roman, and the parallel conflict between the old and the new elites. Nevertheless, the author’s view of this conflict and his assessment of its sides remain a matter of debate. The key to solving it largely lies in a proper understanding of the author’s sympathies and antipathies towards his own characters, borrowed from traditional ancient mythological plots, whose behaviour appears to be a projection onto contemporary events. One such character is Hercules. He appears in two poems at once, Romulea 2 and 4. His image in them breaks many stereotypical ideas about the brutal and tragic nature of this hero; the present article is an attempt to provide an explanation for this. I aim to prove that Hercules is represented as an ambivalent model: on the one hand, he is the embodiment of the Roman side in the Roman-Vandal confrontation for a Roman audience, and on the other hand, he is the model of correct behaviour in conflict in principle. In the latter sense the didactic pathos associated with him could also be addressed to Vandals.